2018
DOI: 10.1111/mec.14563
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen concentration drives local adaptation in the greenlip abalone (Haliotis laevigata)

Abstract: Understanding adaptation has become one of the major biological questions especially in the light of rapid environmental changes induced by climate change. Ocean temperatures are rising which triggers massive changes in water chemistry and thereby alters the living environment of all marine organisms. Studying adaptation, however, can be tricky because spatial genetic patterns might also occur due to random effects, for example, genetic drift. Genetic drift is reduced in very large and well-connected populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A study of the commercially important greenlip abalone (Haliotis laevigata) in Australia provided evidence of local adaptive divergence in a widespread population of a broadcast spawning species. This study, also based on RAD-Seq, found that whereas the majority of the more than 9,000 SNPs in their data set appeared to be selectively neutral, 323 were potentially adaptive (179,180). These potentially adaptive SNP loci were correlated with water temperature and oxygen concentration, and gene annotation showed that three-quarters of these SNPs were associated with genes related to high temperature and low oxygen tolerance.…”
Section: Abalonementioning
confidence: 84%
“…A study of the commercially important greenlip abalone (Haliotis laevigata) in Australia provided evidence of local adaptive divergence in a widespread population of a broadcast spawning species. This study, also based on RAD-Seq, found that whereas the majority of the more than 9,000 SNPs in their data set appeared to be selectively neutral, 323 were potentially adaptive (179,180). These potentially adaptive SNP loci were correlated with water temperature and oxygen concentration, and gene annotation showed that three-quarters of these SNPs were associated with genes related to high temperature and low oxygen tolerance.…”
Section: Abalonementioning
confidence: 84%
“…Genetic shifts associated with abiotic adaptation were a topic of quite a few studies, including the combined effects of phenotypic plasticity and local adaption in allowing lizard adaptation to new climatic regimes (Card, Schield, & Castoe, 2018), local adaptation in abalone (Lampert, 2018) and adaptive evolution following species introductions (Seeb, McKinney, & Seeb, 2018).…”
Section: News and Views Sectionmentioning
confidence: 99%
“…In another study, RADseq data for the greenlip abalone ( Haliotis laevigata ) revealed signs of local adaptation in candidate SNPs associated with genes involved in tolerance to high temperature and low oxygen (Lampert, 2018; Sandoval‐Castillo et al., 2018). These results could influence management of this commercially important species in the face of climate change (Lopez et al., 2019).…”
Section: Introductionmentioning
confidence: 99%